Revisiting Cyber Threats in Government Sectors: A Systematic Review of Attacks, Challenges, and Policy-Level Defenses - Nuraeni, Aisyah; Nugraha, Yudhistira; Aminanto, Muhamad Erza (Indonesian Scientific Journal, 2025)
This paper presents a systematic literature review (SLR) based on the PRISMA framework, synthesizing 128 peer-reviewed studies published between 2020 and 2024, drawn from major scholarly databases. The review investigates cyber threats specifically targeting government institutions and identifies phishing, ransomware, malware, and denial-of-service (DoS) attacks as the most prevalent attack vectors affecting government sector environments. In addition to these threats, the study highlights persistent institutional limitations, such as outdated infrastructure, fragmented inter-agency coordination, limited technical capacity, and regulatory gaps, which hinder effective cybersecurity governance and response. To address these challenges, the review compiles both proactive and reactive mitigation strategies, emphasizing the need for SOC design principles such as scalability, interoperability, inter-agency coordination, and resilience in cyber operations. The paper synthesizes its findings into a taxonomy of threat profiles and contextual constraints, offering a foundational reference for building government-specific SOC models. It also outlines future research directions related to operational validation, capability maturity modeling, and institutional alignment in public-sector cybersecurity architectures.